Cell-Mediated Immune Responses and Immunopathogenesis of Human Tick-Borne Encephalitis Virus-Infection - Blom, Kim; Cuapio, Angelica; Sandberg, J. Tyler; Varnaite, Renata; Michaëlsson, Jakob; Björkström, Niklas K.; Sandberg, Johan K.; Klingström, Jonas; Lindquist, Lars; Gredmark Russ, Sara; Ljunggren, Hans-Gustaf (Frontiers in Immunology, 2018)
Tick-borne encephalitis virus (TBEV) is a flavivirus that belongs to the Flaviviridae family. TBEV is transmitted to humans primarily from infected ticks. The virus causes tick-borne encephalitis (TBE), an acute viral disease that affects the central nervous system (CNS). Infection can lead to acute neurological symptoms of significant severity due to meningitis or meningo(myelo)encephalitis. TBE can cause long-term suffering and has been recognized as an increasing public health problem. TBEV-affected areas currently include large parts of central and northern Europe as well as northern Asia. Mortality rates differ between infections with different TBEV strains. Infection with TBEV triggers a humoral as well as a cell-mediated immune response. In contrast to the well-characterized humoral antibody-mediated response, the cell-mediated immune responses elicited to natural TBEV-infection have been poorly characterized until recently. Here, we review recent progress in our understanding of the cell-mediated immune response to human TBEV-infection. A particular emphasis is devoted to studies of the response mediated by natural killer (NK) cells and CD8 T cells. The studies described include results revealing the temporal dynamics of the T cell- as well as NK cell-responses in relation to disease state and functional characterization of these cells. Additionally, we discuss specific immunopathological aspects of TBEV-infection in the CNS.